Effect of the initial resin distribution in partially impregnated thermoplastic prepregs on consolidation. (7th July 2022) - Boztepe, Sinan; Šimáček, Pavel; Labastie, Karine; Chevalier, Mathieu; Sandre, Patricia; Des, Jean-Marie; Advani, Suresh G.
Abstract: The relation between the initial resin distribution in partially-impregnated thermoplastic UD prepregs and the gas evacuation mechanism as they are consolidated under oven vacuum bagging (OVB) process is explored. To conduct the investigation, carbon fiber (CF) tows were partially impregnated using poly (ether ketone) (PEEK) powders to fabricate three specific prepreg architectures with different surface and through-thickness resin distributions. The initial through-thickness resin distributions, porosity, surface impregnation and surface roughness of the prepregs were measured. Next, OVB consolidation experiments were performed. The effectiveness of gas evacuation and void reduction were quantified based on the initial and the final porosity state of their consolidated laminates. The results show that dry prepreg surfaces provide the most effective gas evacuation through interlayer air pathways, whereas, uniform impregnation in the midzone likely reduces the interconnectedness of voids potentially reducing the ability to evacuate voids both in the through-thickness and the in-plane directions. To achieve void-free consolidation, extra attention must be attributed to design features of prepregs to create more discontinuous through-thickness and surface resin distributions to reduce the distance between dry fiber zones on the surface while maintaining interconnectedness of interlayer and intralayer voids. A preliminary 1D single-ply consolidation model was developed, and a numerical study was carried out. The model predictions were assessed by comparison with single-ply (prepreg) consolidation experiments. It was found that the model gives plausible predictions however the model can be improved by coupling it with other simultaneous phenomena occurring during the consolidation process. Graphical abstract: Image 1